2020
DOI: 10.15252/emmm.201910895
|View full text |Cite|
|
Sign up to set email alerts
|

Follistatin is a novel therapeutic target and biomarker in FLT 3/ ITD acute myeloid leukemia

Abstract: Internal tandem duplication of Fms‐like tyrosine kinase 3 (FLT3/ITD) occurs in about 30% of acute myeloid leukemia (AML) and is associated with poor response to conventional treatment and adverse outcome. Here, we reported that human FLT3/ITD expression led to axis duplication and dorsalization in about 50% of zebrafish embryos. The morphologic phenotype was accompanied by ectopic expression of a morphogen follistatin (fst) during early embryonic development. Increase in fst expression also occurred in adult F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that ovarian cancer cells increase FST production in response to TGF-β stimulation ( 84 ), and FST expression has been shown to coincide with the activation of the signaling cascades downstream of EGF signaling in leukemia cells ( 85 ), however, signaling events driving FST in HNSCC cells remain unknown. Given the enrichment of the EGFR-TGF-β network in our dataset, we hypothesized that HNSCC cells might regulate FST expression in response to both signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that ovarian cancer cells increase FST production in response to TGF-β stimulation ( 84 ), and FST expression has been shown to coincide with the activation of the signaling cascades downstream of EGF signaling in leukemia cells ( 85 ), however, signaling events driving FST in HNSCC cells remain unknown. Given the enrichment of the EGFR-TGF-β network in our dataset, we hypothesized that HNSCC cells might regulate FST expression in response to both signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the FLT3-ITD mutant patients were enriched for CD25+ AML cells, which has also been described previously by others ( 5 , 7 ). It is hypothesized that FLT3-ITD leads to the upregulation of RET , IL2RA and CCL5 through Follistatin ( 44 ), providing some mechanistic basis for the strong association between FLT3-ITD and CD25 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus vectors encoding FST overexpression were prepared as described previously. 30 To establish stable FST-overexpressing LO2 cells, we transfected the cells with the pLJM1‐EGFP (#19319, Addgene, USA) lentivirus vector encoding human FST isoforms (FST317 and FST344). To establish stable FST-knockdown LO2 cells, we transfected the cells with lentivirus vector encoding short hairpin RNA targeting FST (FSTsh), which was designed and produced by Genechem Technology Company (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%